Gamma irradiation with modified atmosphere packaging extend shelf life of mangoes cv. Himsagar - Akhther, N; Islam, MR; Hassan, MK; Mehedi, MNH; Akter, KT (Bangladesh Journal of Nuclear Agriculture, 2023)
Irradiation technology has been in use to prolong shelf life and reduces postharvest losses of agricultural produce in many parts of the world as a safe and commercial option for its high efficacy and safety. The research was carried out at the Postharvest Laboratory of Horticulture Division, BINA during the period from June to July 2021 following completely randomized design (CRD) with three replications of 8 fruits per replication. The preharvest bagged and unbagged mangoes (cv. Himsagor) were collected from Bagha Upazila of Rajshai District. Different doses of gamma irradiation (0, 200, 400, and 600 Gy) were applied, and the irradiated mangoes were wrapped in polypropylene (PP) bags of 35μ thickness along with a control treatment to evaluate shelf life and quality at ambient condition. Parameters investigated were colour, texture, TSS, weight loss, disease incidence, disease severity, and vitamin C content during the period of storage. In terms of combined effect of preharvest bagging and gamma irradiation at the 12th day after storage, the minimum weight loss (3.92%), disease incidence (11.00%) and disease severity (8.61%) were found from pre-harvest bagged mangoes when irradiated @ 400 Gy and wrapped in PP bags. In contrast, the maximum weight loss (18.18%), disease incidence (80.00%) and disease severity (74.67%) were found from the preharvest non-bagged and non-irradiated mangoes that were not wrapped. The findings would greatly contribute in reducing postharvest loss of mangoes and maintain their quality during marketing at ambient condition. Bangladesh J. Nuclear Agric, 37(1): 11-22, 2023